Future and reality of social networks - Estremadoyro, Julio (2013)
In early 2012 it was estimated that one billion people had access to social networks. At the end of the year will be more than double. This growth of over 100 percent human bonding determines that this communication has transformed the Internet and it is now impossible to stop. No activity can be accomplished with world impact and global dissemination unless social networks are used. They are without a doubt a social manifestation with no precedents for the exchange of people, with all the resources of a message: video, audio, text, photos.